2018
DOI: 10.1002/cam4.1505
|View full text |Cite
|
Sign up to set email alerts
|

Major pathologic response and RAD51 predict survival in lung cancer patients receiving neoadjuvant chemotherapy

Abstract: In a previous study, we determined that major pathologic response (MPR) as indicated by the percentage of residual viable tumor cells predicted overall survival (OS) in patients with non‐small‐cell lung cancer (NSCLC) who received neoadjuvant chemotherapy. In this study, we assessed whether two genes and five protein biomarkers could predict MPR and OS in 98 patients with NSCLC receiving neoadjuvant chemotherapy. We collected formalin‐fixed, paraffin‐embedded specimens of resected NSCLC tumors from 98 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…[7][8][9][10] We also reported that combination of MPR with biomarker is a significant predictor of prognosis in patients with NSCLC who received neoadjuvant chemotherapy. 11 The purpose of this retrospective study was to confirm that MPR is predictive of long-term OS in patients with NSCLC treated with neoadjuvant chemotherapy and surgical resection. We also assessed interobserver agreement on MPR between 2 observers and determined the minimum number of slides needed to obtain an accurate determination of tumor response.…”
Section: Introductionmentioning
confidence: 96%
“…[7][8][9][10] We also reported that combination of MPR with biomarker is a significant predictor of prognosis in patients with NSCLC who received neoadjuvant chemotherapy. 11 The purpose of this retrospective study was to confirm that MPR is predictive of long-term OS in patients with NSCLC treated with neoadjuvant chemotherapy and surgical resection. We also assessed interobserver agreement on MPR between 2 observers and determined the minimum number of slides needed to obtain an accurate determination of tumor response.…”
Section: Introductionmentioning
confidence: 96%
“…The present study once again confirms that MPR predicts OS in patients with NSCLC receiving neoadjuvant chemotherapy by identifying a group of patients (PT-MPRþ/LN-MPRþ and PT-MPRþ/LN-MPRÀ) who experienced survival similar to that for patients with complete tumor responses. [13][14][15] These findings suggest that the use of PT-MPR, which was previously markedly correlated with OS in retrospective and prospective studies are applicable to all stages of NSCLC and various histologic tumor types. Furthermore, we found that LN-MPR status alone could predict outcome and that, by stratifying patients into three different groups on the basis of their combined PT-MPR and LN-MPR scores (PT-MPRþ/LN-MPRþ and PT-MPRþ/LN-MPRÀ versus PT-MPRÀ/LN-MPRþ versus PT-MPRÀ/LN-MPRÀ), statistically significant differences in outcome could be observed.…”
Section: Discussionmentioning
confidence: 58%
“…[5][6][7][8] We and others have previously reported that major pathologic response (MPR), defined as residual viable tumor of less than or equal to 10%, can be used as a surrogate end point for survival, thereby shortening the period needed to evaluate novel chemotherapies in clinical trials. [9][10][11][12][13][14][15][16] Currently, many lung cancer trials use MPR to predict drug efficacy after neoadjuvant treatment. In this context, evaluation of tumor viability is typically focused on the primary tumor and scoring of tumor in metastatic sites, such as lymph nodes, has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Researches have investigated and indicated the correlation between complete pathological response and overall survival 9-12 . Other researches also have proved the validity of major pathological response as a surrogate of survival [13][14][15][16] . In this study, the complete response is different between IM and C group (37•5% vs. 7•69%).…”
Section: Clinical Analysismentioning
confidence: 99%